2010
DOI: 10.5209/rev_laza.2010.v31.7
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness of alien vascular plants in six arid zones of Europe, Africa and America

Abstract: Sanz Elorza, M., González Bernardo, F., Serreta Oliván, A. & Gavilán Iglesias, L.P. Invasiveness of alien vascular plants in six arid zones of Europe, Africa and America. Lazaroa 31: 109-126 (2010).Biological invasions are one of the most important components of global change, and have increasing effects on the loss of biodiversity and on human societies as a whole. The difficulties of accurately predicting the fate of a given introduction has led to increased interest in identifying situations where the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
(2 reference statements)
1
3
0
Order By: Relevance
“…The most representative family TA B L E 1 Difference between slopes (Δ) of the linear models of non-native species distributions considering two temporal intervals (2015-2017: higher intervention level (S1-S5); 2018-2019: lower intervention levels (S6-S8)). (Poaceae) in our study is the same dominant non-native plant family found in six other arid regions around the globe (in Africa, America and Europe; Elorza et al, 2010). Also, some species recorded in our study are globally recognized as invasive, such as C. procera, N. glauca, P. aculeata, P. juliflora and R. communis (Richardson & Rejmánek, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…The most representative family TA B L E 1 Difference between slopes (Δ) of the linear models of non-native species distributions considering two temporal intervals (2015-2017: higher intervention level (S1-S5); 2018-2019: lower intervention levels (S6-S8)). (Poaceae) in our study is the same dominant non-native plant family found in six other arid regions around the globe (in Africa, America and Europe; Elorza et al, 2010). Also, some species recorded in our study are globally recognized as invasive, such as C. procera, N. glauca, P. aculeata, P. juliflora and R. communis (Richardson & Rejmánek, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…The taxonomic classification was based on the APG III System (2009), while the spelling of species author names was based on the Species List of Brazilian Flora (2013). Floristic lists included plant habit (herb, vine, shrub or tree, according to Font-Quer [1975]), geographic origin (Duarte et al 2000;Quijano and Pino 2007;Schneider 2007;Silva et al 2007;Biondi and Macedo 2008;Ferreira et al 2009;Oladipupo et al 2009;Sanz-Elorza et al 2010;Vilarreal et al 2010;Araújo et al 2011;Guglieri-Caporal et al 2011;Fabricante and Siqueira-Filho 2012;Fabricante 2013aFabricante , 2013bFabricante , 2013cFabricante , 2014Shirasuna et al 2013), and habitat of establishment (agricultural, ruderal, or natural). Agricultural sites include pasture and cropland areas; ruderal sites represent areas under human influence, such as backyards, gardens, sidewalks, or streets; and natural sites cover the other types of environment, including patches of indigenous vegetation in several conservation conditions.…”
Section: Data Collectionmentioning
confidence: 99%
“…Tamarisk plants exist as shrubs or small trees that are naturally distributed in saline soils of Eurasia, the Mediterranean basin and northern and southwestern Africa (Marlin et al, 2017;Sanz Elorza et al, 2010). Tamarix chinensis Lour is one of the most highly salt-tolerant tree species that is well suited for investigating salt-stress-response genes (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%